Nitrogen Fertilization and Native C4 Grass Species Alter Abundance, Activity, and Diversity of Soil Diazotrophic Communities - Hu, Jialin; Richwine, Jonathan D.; Keyser, Patrick D.; Li, Lidong; Yao, Fei; Jagadamma, Sindhu; DeBruyn, Jennifer M. (Frontiers in Microbiology, 2021)
Native C4 grasses have become the preferred species for native perennial pastures and bioenergy production due to their high productivity under low soil nitrogen (N) status. One reason for their low N requirement is that C4 grasses may benefit from soil diazotrophs and promote biological N fixation. Our objective was to evaluate the impact of N fertilization rates (0, 67, and 202 kg N ha-1) and grass species (switchgrass [Panicum virgatum] and big bluestem [Andropogon gerardii]) on the abundance, activity, diversity, and community composition of soil diazotrophs over three agricultural seasons (grass green-up, initial harvest, and second harvest) in a field experiment in East Tennessee, USA. Nitrogen fertilization rate had a stronger influence on diazotroph population size and activity (determined by nifH gene and transcript abundances) and community composition (determined by nifH gene amplicon sequencing) than agricultural season or grass species. Excessive fertilization (202 kg N ha-1) resulted in fewer nifH transcripts compared to moderate fertilization (67 kg N ha-1) and decreased both richness and evenness of diazotrophic community, reflecting an inhibitory effect of high N application rates on soil diazotrophic community. Overall, cluster I and cluster III diazotrophs were dominant in this native C4 grass system. Diazotroph population size and activity were directly related to soil water content (SWC) based on structural equation modeling. Soil pH, SWC, and C and N availability were related to the variability of diazotrophic community composition. Our results revealed relationships between soil diazotrophic community and associated soil properties, adding to our understanding of the response of soil diazotrophs to N fertilization and grass species in native C4 grass systems.